2013
DOI: 10.3171/2013.2.focus12424
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive hemicraniectomy for spontaneous intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is devastating, with high mortality rates, but its optimum management has not been fully established. Decompressive hemicraniectomy is a surgical procedure used to relieve the malignant elevation of intracranial pressure. The application of decompressive hemicraniectomy in patients with hemispheric ICH has been much less common, although several studies have shown the usefulness of this procedure for large hemispheric ICH. In this review, the present knowledge of the safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 40 publications
4
34
1
6
Order By: Relevance
“…Recently, DHC has been employed even more frequently, owing to studies showing an outcome benefit not only for surgery in large strokes compared to conservative treatment [1,11], but also in older patient cohorts [6]. In broad terms, the basic principle of ICP control is achieved by hemispheric bone removal and incision of the dura (with or without a patch), allowing for sufficient expansion of brain parenchyma [12][13][14][15][16][17][18]; however, the technique lacks a more detailed anatomic recommendation. A craniectomy diameter of 12 cm has been postulated to represent the minimum size for effective decompression, as the incidence of hemicraniectomyassociated lesions increases sharply with defects of smaller size [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DHC has been employed even more frequently, owing to studies showing an outcome benefit not only for surgery in large strokes compared to conservative treatment [1,11], but also in older patient cohorts [6]. In broad terms, the basic principle of ICP control is achieved by hemispheric bone removal and incision of the dura (with or without a patch), allowing for sufficient expansion of brain parenchyma [12][13][14][15][16][17][18]; however, the technique lacks a more detailed anatomic recommendation. A craniectomy diameter of 12 cm has been postulated to represent the minimum size for effective decompression, as the incidence of hemicraniectomyassociated lesions increases sharply with defects of smaller size [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the results of the first STICH trial, several authors have suggested that outcomes could potentially be improved with DC for selected patients with high ICP and mass effect related to ICH. [232][233][234]240 Patients in these studies tended to be those in coma (GCS score <8) and those who had significant midline shift, large hematomas, or ICP that did not normalize with medical management. One study of DC without hematoma evacuation matched 12 consecutive patients with supratentorial ICH to control subjects via propensity score.…”
Section: Craniectomy For Ichmentioning
confidence: 99%
“…Additionally, recent retrospective studies have suggested a possible role for craniectomy in ameliorating increased ICP caused by ICH. [230][231][232][233][234] In addition, the current recommendations do not apply to intracranial hemorrhage caused by trauma or underlying structural lesions such as aneurysms and arteriovenous malformations, because these patients were not included in the described ICH surgery trials.…”
Section: Surgical Treatment Of Ich (Clot Removal)mentioning
confidence: 99%
“…17,36 In addition, when sICH is complicated with hydrocephalus, the placement of an external ventricular drain lowers intracranial pressure and may reduce mortality. 17,37 An external ventricular drain allows for monitoring of intracranial pressure.…”
Section: Type Of Surgerymentioning
confidence: 99%